Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Pemahaman Konsep Matematis - Harefa, Melinia; Harefa, Amin Otoni; Zega, Yulisman (JOEAI (Journal of Education and Instruction), 2023)
The purpose of this study was to improve students' understanding of mathematical concepts on the competence of rational and irrational inequalities through the application of the discovery learning model. The research method used is quantitative method with discovery learning approach, the subject of this research is X TKJ class students of SMK Negeri 1 Tuhemberua. This research took place in two cycles, namely cycle I consisting of 3 meetings and cycle II consisting of 3 meetings. Data collection techniques in this study were observation and objective tests. The instruments used were observation sheets and objective test questions. Based on the results of the study, it was found that the implementation of mathematics learning with the application of the discovery learning model can improve the understanding of mathematical concepts of class X TKJ students of SMK Negeri 1 Tuhemberua on the competence of rational and irrational inequality of one variable. This is based on data obtained through the results of cycle I tests and cycle II tests, the average percentage of students' understanding of mathematical concepts has increased by 15.67%, namely in cycle I of 66.28% and increased to 77.81% in cycle II. The conclusion in this study is that the average percentage of students' understanding of mathematical concepts has increased in cycle I and increased again in cycle II. Based on the qualification guidelines in the percentage table presented in the discussion section, it is classified in the high category. Keywords: discovery learning model, concept comprehension, high school mathematic